The Role of Zakat Funds in Women's Empowerment in Indonesia: A Literature Review - Nashrullah Nashrullah; Efri Syamsul Bahri; Mohd Mizan Aslam (Universitas Negeri Padang, 2025)
This study aims to determine the state of the literature on the role of zakat funds and to examine their role in empowering women in Indonesia through a literature review. This study uses a qualitative method with a descriptive approach and literature study. The literature study uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data is obtained from Google Scholar using the Publish or Perish software, and analyzed using the PRISMA approach. The study's results indicate that zakat funds have a positive impact on women's empowerment across various aspects, particularly in the economic, educational, social, and health domains. Zakat funds contribute to increasing women's financial independence, expanding access to education and skills training, and strengthening women's social and religious roles in their communities.